The changing social worlds of 13-year-olds May 28, 2024 - Smyth, Emer (ESRI, 2024)
This study draws on data on Growing Up in Ireland (GUI) Cohorts '98 and '08 to document changes in the lives of adolescents over the period 2011/12 to 2021/22, building on an earlier study (Smyth, 2022) which compared their experiences at nine years of age. This decade was a period of considerable social and policy change, including reform of the junior cycle, growing digitalisation and the disruption of the pandemic to all aspects of young people's lives. Changes were also evident in the profile of young people and their families, with increasing cultural diversity, higher education levels among parents, lower levels of financial strain and increasing numbers with a disability among members of Cohort '08 than among their older cohort counterparts. The study looks at changes in 13-year-olds' relationships with their parents and peers, in their day-to-day activities and in their experiences of school. The main research questions addressed by the study are: How have the quality of relationships, experience of learning and activities engaged in by adolescents changed over the course of a decade? To what extent do any such changes reflect differences in the family characteristics of the young people? Are any such changes more evident for boys or girls or for young people from different social backgrounds? Is differentiation by gender and social background in adolescents' social worlds less evident for the younger cohort than previously?